Three-year progression-free survival of a patient with concomitant mucinous adenocarcinoma of the colon with peritoneal dissemination and multiple myeloma who received lenalidomide: a case report - Koki Tamai; Hajime Hirose; Yo Akazawa; Yukihiro Yoshikawa; Masatoshi Nomura; Hiroshi Takeyama; Masahiro Tokunaga; Mitsuyoshi Tei; Shu Okamura; Yusuke Akamaru (Surgical Case Reports)
Abstract Background Concomitant multiple myeloma (MM) and other primary malignancies is rare. Therefore, the treatment outcomes of patients with these conditions have not been well discussed. Lenalidomide is an oral thalidomide analog drug used for MM. Recently, the antitumor effect of lenalidomide has been gaining attention, and lenalidomide has been applied for managing solid tumors. The current case showed the treatment course of a patient treated with lenalidomide for concomitant MM and colon cancer with peritoneal dissemination. Case presentation A 74-year-old female patient receiving treatment for MM was diagnosed with mucinous adenocarcinoma of the transverse colon. The patient was clinically diagnosed with stage IIIC T4aN2M0 disease. Subsequently, laparoscopic colectomy with lymph node dissection was planned. However, intraperitoneal observation revealed peritoneal dissemination that had sporadically and widely spread. Therefore, palliative partial colectomy was performed to prevent future hemorrhage or obstruction. The patient was discharged on the 10th postoperative day without postoperative complication. Based on the patient’s preference, lenalidomide was continually administered for MM without systemic chemotherapy. The patient survived for > 36 months without any signs of tumor progression. Conclusion The current case first showed the treatment course of concomitant MM and colon cancer. The antitumor effect of lenalidomide can possibly contribute to 3-year progression-free survival in patients with mucinous adenocarcinoma of the colon with peritoneal dissemination.